Estudo da remoção e toxicidade dos pesticidas atrazina e oxifluorfem pela cianobactéria "Microcystis novacekii" em condições de cultivo. - Marcela Maria de Castro Campos (2009)
Water contamination by pesticides due to anthropogenic activities has become a global concern in terms of environmental damage and public health. The cyanobacteria are microrganisms capable of growing in polluted environments and their potential as agents of bioremediation of contaminated environments is promising. This study aimed to evaluate the potential for removal of the pesticides atrazine and oxyfluorfen by the cyanobacteria Microcystis novacekii and their toxicity in a laboratory culture. The biodegradation test was conducted in five concentrationsof each pesticide in the culture medium WC (water culture) for 96 hours and quantitative analysis by gas chromatography coupled to detection ofnitrogen/phosphorus and electron capture. The cyanobacteria showed potential for atrazine degradation of the medium in concentrations equal or greater than 50ìg/L, with average removal of 22.2% in 96 hours. In lower concentrations, 25 ìg/L, the degradation did not occur in significant values, suggesting the existence of a minimum concentration of the herbicide for activation of cellular metabolic processes. The oxyfluorfen showed significantly lower concentrations at the beginning of theexperiment in the presence of cyanobacteria and a pronounced spontaneous degradation in the control group at the end of the experiment, indicating that others mechanisms for degradation is likely to happen, as photolysis. Regarding toxicity, Microcystis novacekii shown to be tolerant to high concentrations of pesticides, and the EC50 (96 hours) 4.2 mg/L and 17.6 mg/L for atrazine and oxyfluorfen, respectively, confirming the resistance of the specie. The results of this study maysupport further work to evaluate the potential of Microcystis novacekii as a future bioremediation agent of environments contaminated with these and other pesticides.